2021
DOI: 10.1038/s41467-021-24417-w
|View full text |Cite
|
Sign up to set email alerts
|

Self-rechargeable cardiac pacemaker system with triboelectric nanogenerators

Abstract: Self-powered implantable devices have the potential to extend device operation time inside the body and reduce the necessity for high-risk repeated surgery. Without the technological innovation of in vivo energy harvesters driven by biomechanical energy, energy harvesters are insufficient and inconvenient to power titanium-packaged implantable medical devices. Here, we report on a commercial coin battery-sized high-performance inertia-driven triboelectric nanogenerator (I-TENG) based on body motion and gravity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(92 citation statements)
references
References 36 publications
0
92
0
Order By: Relevance
“…In addition, the performance evaluation criterion of textile TENGs should still consider the special structural effect and wearing performance of textiles. (5) The application terminal of textile TENGs is the human body, which not only needs to have a high degree of fitness to meet the diverse and complex human motion and external environment variations but should also bring certain comfort and satisfaction to the daily wearing of the human body. Therefore, for the material selection of textile TENGs, it is best to choose materials with good affinity to human skin to avoid toxic materials or materials that will cause itching to human skin.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the performance evaluation criterion of textile TENGs should still consider the special structural effect and wearing performance of textiles. (5) The application terminal of textile TENGs is the human body, which not only needs to have a high degree of fitness to meet the diverse and complex human motion and external environment variations but should also bring certain comfort and satisfaction to the daily wearing of the human body. Therefore, for the material selection of textile TENGs, it is best to choose materials with good affinity to human skin to avoid toxic materials or materials that will cause itching to human skin.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…In general, the power needed to operate millions of wearable sensors is very small, typically at the microwatt to watt level. Although orderly energy supply modes can provide a part of the power for distributed electronic devices, the rest of the power must be provided by random energy sources in our living environment, including solar energy, vibration, motion, wind energy, and other resources [3][4][5][6][7][8][9]. What we expect is to make full use of any available resources in the environment where the device is deployed.…”
Section: Introductionmentioning
confidence: 99%
“…The TENG generated a maximum V oc of 65.2 V and energy of 0.495 µJ during each cardiac motion cycle, which is above the endocardial pacing threshold energy of 0.377 µJ. In a mongrel in vivo model, a five-staged TENG was shown to charge a lithium-ion battery by harvesting biomechanical body and gravity motion of a subcutaneous implantation site and enable ventricle pacing and sensing operation mode of the self-rechargeable cardiac pacemaker system [ 31 ]. TENGs can produce high voltage outputs but the gap between the friction layers needs to be protected from body fluids, otherwise it will significantly affect the output performance.…”
Section: Biomechanical Energy Harvestingmentioning
confidence: 99%
“…With the popularity of smart skin, TENG came into view due to its superior biocompatibility and portability. More and more research has been conducted on TENG in the smart skin field [57,58]. As shown in Figure 8a, Cao et al [59] demonstrated a TENG for intelligent electronic skin using a fish bladder membrane as friction.…”
Section: Application Of Teng In the Smart Skin Fieldmentioning
confidence: 99%